Alih Kode Pada Anime Great Pretender Karya Ryota Kosawa - Febri, Nada Fadiya; Putri, Meira Anggia (Universitas Negeri Padang, 2024)
Code-switching involves the transition between different language varieties or between different languages. This phenomenon occurs in anime, particularly in the anime